2014
DOI: 10.1039/c3tc32235a
|View full text |Cite
|
Sign up to set email alerts
|

Electrical characterization of nanocrystal solids

Abstract: Here we provide a primer for correctly selecting and implementing optoelectronic characterization techniques on semiconductor nanocrystal solids and choosing the appropriate models with which to interpret the data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 75 publications
1
25
0
Order By: Relevance
“…Bozyigit et al . studied trap states in meta-semiconductor-metal diodes (ITO/PbS-EDT/LiF/Al), and concluded that the trap states is independent of the ITO/PbS QDs interface and can even pin the Fermi-level20212223. Recently Chuang et al .…”
mentioning
confidence: 99%
“…Bozyigit et al . studied trap states in meta-semiconductor-metal diodes (ITO/PbS-EDT/LiF/Al), and concluded that the trap states is independent of the ITO/PbS QDs interface and can even pin the Fermi-level20212223. Recently Chuang et al .…”
mentioning
confidence: 99%
“…e,avg F F (9) or equivalently via ρ(E F ) = (Nc h (E F )) −1 ·(dk h,avg (E F ))/dE F , as shown in the Supporting Information. As the electron trapping rates could be determined with greater accuracy, we chose the derivation from electron trapping rates.…”
Section: Nano Lettersmentioning
confidence: 98%
“…The current focus of much research remains in deep understanding of trap associated charge transport behaviour in PbS NCs and their role in influencing the device performance. [30][31][32][33]45,46 As the gain is principally achieved via a prolonged carrier lifetime this limits the temporal response of the device that requires a fast recombination and subsequent collection of charge carriers. This sets up a fundamental trade-off between photoconductor gain and the bandwidth.…”
Section: Pbs Nanocrystal Photodetectorsmentioning
confidence: 99%